Вальтер Скотт в українських перекладах та критиці - Попадинець, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The author of the paper reconstructs the evolution of Walter Scott’s inheritance perception in Ukrainian literature and criticism. The stages of this process are also revealed in the article.